Sleep problems in elderly patients with rheumatoid arthritis: Contributing factors and quality of life implications - Neslihan Kayahan Satış; Hasan Satış (Ulusal Romatoloji Dergisi)
Objective: Sleep-related problems are common in rheumatoid arthritis (RA) patients of advanced age. This study aimed to identify factors contributing to poor sleep quality in elderly RA patients and assess their impact on quality of life. Methods: This study included RA patients aged ≥65 years, admitted to a rheumatology clinic between May and September 2024, using a cross-sectional design. The Pittsburgh Sleep Quality index (PSQI) was used to evaluate sleep, while RA activity was measured via disease activity score 28-C-reactive protein (DAS28-CRP), and quality of life was assessed with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30. A multivariate regression analysis was used to identify factors associated with poor sleep quality. Results: The study included 77 elderly RA patients (mean age 70.8±4.9 years, 59.8% female). The median DAS28-CRP score was 4.3, and 75.3% were not in remission. A total of 50.65% of the patients had poor sleep quality (PSQI >5). In the multivariate analysis, age ≥75 years [odds ratio (OR)=8.23, 95% confidence interval (CI) (1.51-44.77), p=0.015], being single [OR=4.63, 95% CI (1.17-18.36), p=0.029], active RA [OR=5.65, 95% CI (1.44-19.99), p=0.035] and depression [OR=5.04, 95% CI (1.17-21.73), p=0.030] were associated with poor sleep quality. Physical, emotional, and role function scores as well as fatigue, pain, and insomnia symptoms were observed at worse levels in the group with poor sleep quality. Conclusion: Our study emphasizes the significance of managing sleep disorders in elderly RA patients. Disease activity and psychosocial factors are closely linked to sleep problems, which can be addressed to improve sleep quality and overall quality of life.